Noninvasive and Multidisciplinary Approach to the Functional and Esthetic Rehabilitation of Amelogenesis Imperfecta: A Pediatric Case Report - Juliana Feltrin de Souza; Camila Maria Bullio Fragelli; Marco Aurélio Benini Paschoal; Edson Alves Campos; Leonardo Fernandes Cunha; Estela Maris Losso; Rita de Cássia Loiola Cordeiro (Hindawi Limited, 2014)
Case Report. An 8-year-old girl with amelogenesis imperfecta (AI) reported unsatisfactory aesthetics, difficulty in mastication, and dental hypersensitivity. The intraoral examination observed mixed dentition, malocclusion in anteroposterior relationships, anterior open bite, and dental asymmetry. A hypoplastic form of AI was diagnosed in the permanent dentition. A multidisciplinary planning was performed and divided into preventive, orthopedic, and rehabilitation stages. Initially, preventive treatment was implemented, with fluoride varnish applications, in order to protect the fragile enamel and reduce the dental sensitivity. In the second stage, the patient received an interceptive orthopedic treatment to improve cross-relationship of the arches during six months. Finally, the rehabilitation treatment was executed to establish the vertical dimension. In the posterior teeth, indirect composite resin crowns were performed with minimally invasive dental preparation. Direct composite resin restorations were used to improve the appearance of anterior teeth. Follow-Up. The follow-up was carried out after 3, 6, 12, and 18 months. After 18 months of follow-up, The restoration of integrity, oral hygiene, and patient satisfaction were observed . Conclusion. Successful reduction of the dental hypersensitivity and improvement of the aesthetic and functional aspects as well as quality of life were observed.